Ecology of weeds and invasive plants relationship to agriculture and natural resource management - Radosevich, Steven R.; Holt, Jodie S.; Ghersa, Claudio (Wiley-Interscience, 2007)
"The Third Edition of the authoritative reference gives readers an in-depth understanding of how weeds and invasive plants develop and interact in the environment so they can manage and control them more effectively. The guide includes an introduction to weeds and invasive plants in various environments and an overview of their ecology and evolution." "This is the definitive, hands-on reference for land managers and professionals in plant sciences, agronomy, weed science, and horticulture. It is also a textbook for senior undergraduate or graduate students studying agriculture, ecology, natural resources management, environmental management, or related fields."--BOOK JACKET